Sustainable Soil Health Management through Conservation Agriculture - Singh, V K; Rathore, S S; Shekhawat, Kapila; Singh, Rajeev K (Indian Farming, 2017)
CA involves the application of modern agriculture tools to improve production, enables not only the maximization of yields but also helps maintain the health and integrity of the agri-ecosystem unlike the traditional systems which mainly aim to maximize yields often at the cost of the environment. Expansion of conservation agriculture can create a win-win situation.